Can Match-Mimicking Intermittent Practice Be Used as a Simulatory Training Mode of Competition Using Olympic Time Frame in Elite Taekwondo Athletes? - Chuang, Sheng-Ju; Sung, Yu-Chi; Chen, Chung-Yu; Liao, Yi-Hung; Chou, Chun-Chung (Frontiers in Physiology, 2019)
Aim: The physiological realities between Taekwondo (TKD) simulation kicking training and TKD competition according to Olympics time-frame remains unclear. The purpose of this study is to establish an Olympic match-simulated kicking model and compare its effects with the real TKD competition on physiological challenges and hormonal responses during serial matches in elite athletes. Method: Sixteen elite TKD athletes randomly assigned into either TKD match-simulated kicking group (TMSK; N = 8, age: 21.3 ±0.2 yrs) or simulated TKD competition group (STC; N = 8, age: 21.6 ±0.5 yrs). Both groups performed either simulated kicking or TKD competitions in the same time-course order, and all physiological parameters and blood sampling time-points were identical between groups. The heart rate (HR) and rating of perceived exertion (RPE) were recorded during each match-simulated kicking and TKD competition sessions. Blood samples were obtained at before competition (Pre-Comp.), competition of 4-consecutive matches (End-Comp.), and 24-hours after the first match (Next day) for determination of biomarkers of muscle damage (myoglobin and CK), hematological profiles, and hormonal profiles (testosterone and cortisol). Results: The responses of HR, RPE, blood lactate levels during the consecutive testing sessions showed no differences between TMSK and STC. The changes in CK and myoglobin were greater in STC (p < 0.05), and the greater decreases in red blood cells (RBC) loss was observed in STC group (p < 0.05). Compared with TMSK, the inflammatory state reflecting by the ratios of neutrophils-to-lymphocyte (NLR) and platelets-to-lymphocyte (PLR) were higher in STC (p < 0.05). Moreover, the catabolic state (cortisol/testosterone) was greater in STC than in TMSK (p < 0.05). Conclusion: We demonstrated that, in compared with TMSK, the STC produced greater muscle damage, inflammatory responses, and catabolic stress in the consecutive Olympic competition time-frame in elite male TKD athletes. Although TMSK is capable of eliciting similar physiological challenges to the extent of TKD competition, yet the muscle damage and hormonal profiles provoked by TMSK was not comparable to the TKD competition. Our findings provide a scientific-based fundamental information and better understanding for coaches, athletes, and sports scientists to develop TKD-specific training program for Olympic preparation.